Brazil´s role in South-American integration during the governments of Fernando Henrique Cardoso (1995-2002) and Luiz Inácio “Lula” da Silva (2003-2010): a comparative analysis - Borges, Fábio (Geopolítica(s). Revista de estudios sobre espacio y poder, 2012)
This article assesses Brazil´s relations to South-American countries in the period comprising Fernando Henrique Cardoso (1995-2002) and Lula da Silva´s (2003-2010) terms. Brazilian foreign policy principles during both presidencies will be studied, and similarities and differences identified through the gaze of Brazil´s main foreign policy makers and policy analysts at that time. It is possible to point at a convergence of interests between diplomats and certain Brazilian business sectors, specially construction companies which operate in South America. The logics of the Initiative for the Integration of Regional Infrastructure in South America (IIRSA), proposed by Brazil in 2000 at the first meeting in history of South-American presidents, shows the proximity of interests between the diplomacy and Brazilian businessmen. At the end of the article we will offer some final reflections on the successes and the limitations of Fernando Henrique Cardoso and Lula´s foreign policies vis à vis South-American countries.
Keywords: Brazil; South America; autonomy; consensual hegemony; IIRSA; territorial impacts